2019
DOI: 10.3390/molecules24061095
|View full text |Cite
|
Sign up to set email alerts
|

Defining Processing Times for Accelerator Produced 225Ac and Other Isotopes from Proton Irradiated Thorium

Abstract: During the purification of radioisotopes, decay periods or time dependent purification steps may be required to achieve a certain level of radiopurity in the final product. Actinum-225 (Ac-225), Silver-111 (Ag-111), Astatine-211 (At-211), Ruthenium-105 (Ru-105), and Rhodium-105 (Rh-105) are produced in a high energy proton irradiated thorium target. Experimentally measured cross sections, along with MCNP6-generated cross sections, were used to determine the quantities of Ac-225, Ag-111, At-211, Ru-105, Rh-105,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The radiopurity of 225 Ac will likely be the first specification that fails. The Trilab team has estimated the radiopurity post purification in the presence of 227 Ac and 227 Ac and daughters for BLIP produced 225 Ac from Th targets 18 . Removal of 223 Ra and 227 Th would increase the radiopurity of 225 Ac produced from a Th target at BLIP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiopurity of 225 Ac will likely be the first specification that fails. The Trilab team has estimated the radiopurity post purification in the presence of 227 Ac and 227 Ac and daughters for BLIP produced 225 Ac from Th targets 18 . Removal of 223 Ra and 227 Th would increase the radiopurity of 225 Ac produced from a Th target at BLIP.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported herein seek to synthesize, characterize, and evaluate PCST inorganic ion exchanger in the separation process of 225 Ac from irradiated Th target. During the accelerator production of 225 Ac from a 232 Th target 227 Ac and the daughters of 227 Ac are coproduced 18 . The daughters of 227 Ac ( 227 Th and 223 Ra) can be separated from 225 Ac during the purification process 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches are currently underway to find out alternative methods to produce 225 Ac. For example, the Tri-lab project team is looking into ways to directly extract 225 Ac from a proton-irradiated thorium target, and produced 81.4 GBq of 225 Ac in a 10-day irradiation of 200 MeV proton beam at 165 μA 10 , 11 . Regarding this method, one concern is ~ 0.3% yield of 227 Ac contaminating 225 Ac in addition to the relatively high proton energy required.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of fission products/ 225 Ac is 12:1, and the radionuclides that are produced are from all the different groups in the periodic table [11]. During the proton irradiation of a thorium target, 227 Ac and 226 Ac are coproduced, and recently published literature discusses their impact on production [12].…”
Section: Introductionmentioning
confidence: 99%